IMPLEMENTASI PROGRAM DESA MAJU INHIL JAYA (DMIJ) BIDANG SARANA INFRASTRUKTUR DESA BATANG TUMU KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR TAHUN 2017-2019 - Aandriannto "; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Maju Inhil Jaya Village Program is a program of the Indragiri Hilir Regency Community and Village Empowerment Service (DPMD) implemented by the villages of the Indragiri Downstream district which aims to improve the welfare and employment opportunities of rural communities by encouraging independence in decision making and management of sustainable development. The problem in this study is that the implementation of the Advanced Inhil Jaya Village program in the field of infrastructure has not been optimal due to several factors supporting the performance of policy implementation that have not been maximized. The purpose of this study was to determine the Implementation of the Maju Inhil Jaya (DMIJ) Village Program in the Field of Infrastructure Facilities in Batang Tumu Village, Mandah District, Indragiri Hilir Regency in 2017-2019. The purpose of this study is to analyze and also describe the implementation of the Advanced Inhil Jaya Village (DMIJ) program in the field of infrastructure facilities in Batang Tumu Village, Mandah District, Indragiri Downstream Regency in 201-2019. This research is a type of descriptive research. Data collection techniques using interviews, observation and documentation as well as data analysis techniques in this study were qualitative. The results of this study are that the implementation of the Advanced Inhil Jaya Village Program (DMIJ) in the field of infrastructure facilities in Batang Tumu village, Mandah sub-district, Indragiri downstream district in 2017-2019 has not been optimal, based on the findings of researchers in the field the influence of implementing actors and lack of budget. Regarding the others, it went well even though it was not without flaws. Keywords: Implementation, Policy Implementation, Policy Content, Policy Environment, DMIJ Program.